Prinsip Kerja Sama dalam Naskah Drama Bila Mencintai Dayang Tari Karya Benny Arnas - Inda Puspita Sari; Hartati Ratna Juita (LP4MK STKIP PGRI Lubuklinggau, 2019)
The purpose of this study was to describe the principle of cooperation in Drama Manuscripts Bila Mencintai Dayang Tari by Benny Arnas. The research method used is a qualitative descriptive method. The data source in this study is a one-round drama script Bila Mencintai Dayang Tari by Benny Arnas. Data analysis in this study included data reduction, data presentation and conclusion. The results of the study showed that the principle of cooperation used in the drama script Bila Mencintai Dayang Tari by Benny Arnas was dominated by the use of quality maxims in each dialogue. In addition, the maxim of quantity, the maxim of relevance, and the maxim of implementation are used. Maximized quality, quantity maxim, relevance maxim, and implementation maxims used in drama scripts show that directly between speakers and spoken partners provide information as desired between the two so as to provide readers with a good understanding.